Debriefing evaluation in nursing clinical simulation: a cross-sectional study - Carina Bortolato-Major; Maria de Fátima Mantovani; Jorge Vinícius Cestari Felix; Radamés Boostel; Ângela Taís Mattei da Silva; Jaime Alonso Caravaca-Morera (Revista Brasileira de Enfermagem)
ABSTRACT Objective: Evaluate the contribution of debriefing after clinical simulations for nursing students. Method: Quantitative study, conducted with 35 nursing students who participated in five clinical simulation scenarios with planned debriefings based on the model of the National League Nursing/Jeffries Simulation Theory. After the fifth scenario, students answered the Debriefing Evaluation Scale associated with the Simulation. Results: The items evaluated involved the psychosocial, cognitive, and affective values, and within a scale from one to five, the highest mean was found in cognitive value with 4.23 (±0.56) points, then in psychosocial value with 3.77 (±0.53), and finally in affective value with 3.71 (±0.63) points. Conclusion: The debriefing conducted after the clinical simulation scenarios was a reflective exercise that contributed to the student integrating multiple knowledges in affective, cognitive and psychosocial values, and thus develop the competencies required.